PERANCANGAN ULANG RANGKA DEPALLETIZER UNTUK MENINGKATKAN KEKAKUAN DAN MENURUNKAN TEGANGAN DI PT X - Reno Ade Maulana; Ahmad Saepuddin (Steam Engineering, 2026)
The depalletizer frame structure plays a crucial role in maintaining system motion stability during material handling processes in production lines. The existing frame design utilizes angle steel (open section), which has lower moment of inertia and torsional stiffness compared to closed sections, making it prone to larger deformation under operational loading. This study aims to redesign the depalletizer frame structure by replacing the angle section with a hollow (closed section) profile made of ASTM A36 steel and to evaluate its structural performance using Finite Element Analysis (FEA). The main contribution of this study is the quantitative demonstration that the use of hollow sections significantly improves the structural stiffness of the depalletizer frame. The results show a reduction in maximum displacement of 79.97%, from 2.86 mm to 0.573 mm under the most critical loading condition, and a reduction in von Mises stress of 29.13%, from 162 MPa to 114.817 MPa. In addition, the safety factor increases from 1.54 to a minimum of 2.18. Fatigue analysis indicates that the redesigned structure achieves a total life of 1,000,000 cycles, representing a significant improvement of 26.6% compared to the existing design, which has a minimum total life of 790,075.8 cycles. For all loading variations, the displacement values remain below the critical limit of 1.0 mm and the minimum safety factor exceeds 1.5, indicating that the redesigned structure satisfies the required stiffness and operational safety criteria. These findings demonstrate that the use of hollow sections provides design advantages in terms of increased structural stiffness, simplified frame configuration, reduced number of welded joints, and improved reliability and stability of depalletizer systems.